UPAYA PENINGKATKAN HASIL BELAJAR PENGERJAAN SOAL CERITA MATERI PECAHAN DENGAN MODEL PROBLEM BASED LEARNING SISWA KELAS III D SD ST. IGNATIUS MEDAN T.P. 2023/2024 - Manik, Kompina (Quaerite Veritatem : Jurnal Pendidikan, 2024)
This study aims to improve student learning outcomes in teaching Fraction Material story problems in class III D SD St. Ignatius Medan Learning Year 2023/2024. The method in this research is Classroom Action Research (PTK) through the use of the Problem Based Learning learning model which is carried out in two cycles. This research is in the form of Classroom Action Research which is carried out with two cycles, each cycle consists of one meeting. The research subjects were class III-D SD St. Ignatius Medan with 27 students consisting of 12 boys and 15 girls. Data collection techniques were carried out using observation, tests, and documentation. Based on the data analysis that has been done previously, it is known that the results of Mathematics Learning are still low in class III of St. Ignatius Elementary School. The results of the study showed an increase in each cycle, this can be seen from the pre-cycle test results obtained an average of 61.11 with learning completeness of 29.63%. In cycle I obtained an average of 72.96 with 51.85% learning completeness and cycle II obtained an average of 90.92 with 92.59% learning completeness. So it can be concluded that by applying the Problem Based Learning Model can improve the learning outcomes of students in class III D SD St. Ignatius Medan Lesson Year 2023/2024 working on story problems on Fraction Material.